Renal sarcoidosis: a rare case. Issue 1 (14th December 2018) - Menezes, Maria; Patarata, Eunice
Abstract : Sarcoidosis is a multisystemic granulomatous disease with rare renal involvement. We describe a case of a 45-year-old female patient admitted to the hospital with severe acute kidney injury and uveitis. After clinical investigation, sarcoidosis with renal, hepatic and ocular involvement was diagnosed. Renal biopsy revealed acute granulomatous interstitial nephritis and treatment with systemic corticosteroids was started with marked improvement in renal function.